Learn OpenShift : Deploy, build, manage, and migrate applications with OpenShift Origin 3.9 /: Deploy, build, manage, and migrate applications with OpenShift Origin 3.9. (2018) - Zuev, Denis; Usov, Aleksey; Kropachev, Artemii
No abstract available